AI-BASED APPROACH TO RISK MANAGEMENT IN SUPPORT OF SUSTAINABLE DEVELOPMENT GOALS - Franciskus Antonius Alijoyo (RADJA PUBLIKA, 2025)
Artificial intelligence (AI)-based approaches to risk management have shown great potential in supporting the achievement of sustainable development goals. AI provides the ability to detect, analyse and respond to risks much more effectively than traditional methods due to its ability to process data from multiple sources with high speed and accuracy. The integration of AI enables better identification of risk patterns, thereby increasing responsiveness and adaptability in addressing global challenges. However, the application of AI also requires attention to data quality, as well as the risk of algorithmic bias, which demands human oversight and deep ethical considerations. With the right management strategy, AI can play a key role in ensuring more efficient, equitable and inclusive sustainable development.